Association between bedtime and the prevalence of newly diagnosed non‐alcoholic fatty liver disease in adults. (29th June 2018) - Wang, Honglei; Gu, Yeqing; Zheng, Lixiao; Liu, Li; Meng, Ge; Wu, Hongmei; Xia, Yang; Bao, Xue; Shi, Hongbin; Sun, Shaomei; Wang, Xing; Zhou, Ming; et al.
Abstract: Background & Aims: Emerging evidence supported that circadian clocks played an important role in the development and progression of non‐alcoholic fatty liver disease (NAFLD). Bedtime is a strong regulator of circadian rhythms, implying that it may contribute to the onset of NAFLD. However, few studies have examined the association between bedtime and NAFLD. The purpose of the study was to determine whether late bedtime is associated with newly diagnosed NAFLD in an adult population. Methods: This population‐based study was performed in 22 807 participants in Tianjin, China. Bedtime was obtained from a self‐administered questionnaire, and NAFLD was diagnosed by abdominal ultrasonography. Odds ratios of NAFLD for bedtime categories were estimated with multiple logistic regression models. Results: The prevalence of newly diagnosed NAFLD was 18.8% in the present study. After adjustment for the potential confounders, compared with the reference group (bedtime ≤22:00), the odds ratios (95% confidence intervals) of NAFLD were 1.18 (1.05‐1.32) and 1.42 (1.21‐1.68) for bedtime from 22:00 to 24:00 and ≥24:00, respectively. Conclusion: Late bedtime was slightly but significantly associated with an increased prevalence of newly diagnosed NAFLD, independently of confounding factors. It is suggested that early bedtime may be beneficial in preventing NAFLD.